ANALISIS FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PADA BANK PERKREDITAN RAKYAT PT. MODERN EXPRESS CABANG PIRU KABUPATEN SERAM BAGIAN BARAT - Margareth E. Leiwakabessy (Soso-Q : Jurnal Manajemen, 2019)
The purpose of this study was to determine the effect simultaneously or partially between Credit Interest Rates, Third Party Funds (DPK), and Non Performing Loans (NPLs) on Modern Express BPR lending in the Western Region of Piru Seram Branch in 2016 - 2017 (Monthly ). The choice of multiple regression in addition to seeing the effect between the independent variables and related variables is also because the independent variables in the study amounted to more than one.Based on the research, the results show that the Lending Rate (SBK) has a significant effect on lending at BPR Modern Express. Community Deposits (DPK) have no significant effect on lending at BPR Modern Express. Non-Current Credit (NPL) has no significant effect on lending at BPR Modern Express. While simultaneously the Credit Interest Rate (SKB), Community Deposits (DPK) and Non-Current Credit (NPL) significantly influence the lending at BPR Modren Express in the Western Piru Seram Branch. Keywords: Credit Interest Rates (SBK), Community Deposits (DPK), Non-Current Credit (NPL) and Credit Distribution.